Psychological factors of diet quality among rural populations of Latin America during the COVID-19 pandemic: a cross-sectional study - Durán-Agüero, Samuel (2022)
“Introduction: This study aimed to determine the relationship between symptoms of anxiety and/or anhedonia (inability to feel pleasure) and diet quality during confinement due to COVID-19 in rural populations in Latin America. Methods: This was a multicentric, cross-sectional study. An online survey was applied, which included the Beck Anxiety Inventory, Snaith-Hamilton Pleasure Scale for assessing the presence of anhedonia, the Food Intake Questionnaire and sociodemographic questions. Results: The study included 10 552 people from 11 countries; 708 participants were living in rural areas. More than half of the participants were quarantined at the time of the survey. Diet quality was inversely associated with anhedonia (p<0.001) and anxiety (p=0.003). In addition, a healthier diet was associated with being female (p=0.030), having a higher level of education (p=0.008) and country of residence (p=0.001). Conclusion: Among the rural population during the COVID pandemic, this study found a worse diet quality was associated with symptoms of anhedonia and anxiety, as well as lower level of education and being male. Proposals to improve the quality of the diet could include interventions aimed at people's mental health.“